The light charged particle detector array at the CSNS Back-n white neutron source. (1st April 2023) - Sun, Kang; Zhang, Guohui; Yi, Han; Fan, Ruirui; Tang, Jingyu; Jiang, Wei; Chen, Yonghao; Jiang, Haoyu; Cui, Zengqi; Hu, Yiwei; Liu, Jie; Ning, Changjun; et al.
Abstract: The Back-n white neutron source at the China Spallation Neutron Source (CSNS) provides neutrons in the continuous energy region from 0.5 eV to 200 MeV. A spectrometer named Light charged Particle Detector Array (LPDA) is designed for the study of (n, lcp) reactions at Back-n. The main detector of the LPDA spectrometer, a 16-unit Δ E -Δ E - E telescope array, is composed of two arrays of 8-unit Δ E -Δ E - E   telescope. Each telescope unit consists of a Low-Pressure Multi-Wire Proportional Chamber (LPMWPC), a Si-PIN detector, and a CsI(Tl) scintillator detector. In 2021, a neutron-proton ( n - p ) scattering reaction cross-section measurement experiment was accomplished as the first experiment of the telescope array. Protons can be clearly identified in the Δ E - E spectrum (LPMWPC + Si-PIN) and the Δ E - E spectrum (Si-PIN + CsI(Tl)). Cross sections of the n - p scattering reaction in the neutron energy range of several MeV are extracted. The Δ E - E method also provides new measurement opportunities for many-body neutron induced light charged-particle emission reactions.